A case of rectal neuroendocrine carcinoma in a patient with long‐standing ulcerative colitis involving alterations of the p16‐Rb pathway. Issue 10 (29th August 2017) - Norose, Tomoko; Ohike, Nobuyuki; Imai, Hideyuki; Shibata, Hideki; Suzuki, Reika; Isobe, Tomohide; Asonuma, Kunio; Kuroki, Yuichiro; Nagahama, Masatsugu; Tanaka, Jun‐ichi; Takimoto, Masafumi
Abstract : The patient was a 54‐year‐old male who had been suffering from extensive ulcerative colitis (UC) for 17 years. Colonoscopy revealed an elevated lesion in the affected rectum, and its biopsy demonstrated neuroendocrine carcinoma (NEC). The surgical specimen obtained on laparoscopic high anterior resection showed extensive active inflammatory and dysplastic lesions and three grossly visible multifocal malignant lesions: a polypoid fungating tumor of NEC (type 1, 20 mm in diameter, pT3) that had been preoperatively noticed, a polypoid fungating tumor of adenocarcinoma (type 1, 22 mm, pT2) and a protruded sessile polypoid tumor (0–Is, 5 mm, pTis) of adenocarcinoma. The NEC was adjacently accompanied by dysplasia‐carcinoma sequential lesions and showed a diffuse immunohistochemical overexpression of p53 and p16 proteins and the loss of Rb with no abnormal immunohistochemical staining of microsatellite instability markers and no KRAS mutations. Fifteen months later, the patient showed liver metastasis from the NEC component, followed by bone and spinal metastasis; he died 22 months after the initial diagnosis. A rare case of lethal NEC arising from long‐standing extensive UC was reported. The NEC appeared to be UC‐related, not incidental, and complicated by progression from dysplasia to carcinoma involving alterations of the p16‐Rb pathway.